Penguatan Kegiatan Kolaboratif Orang Tua dan Anak melalui Pembuatan Stik Keluarga - Nabilla, Resya; Arvina, Rianti; Marefia, Asyifa; Indriyani, Jupita; Ramadhani, Nabila Putrii; Utami, Winda Sherly; IndryanI (Belalek, 2025)
This community service activity aims to strengthen parent–child collaboration through the creative activity of making “Family Sticks” at TK Al-Ghifari. Using a participatory method, the program was conducted in three stages: preparation, implementation, and evaluation. During the implementation, parents received material on the family’s role in early childhood education, followed by a collaborative craft activity using family-themed stick figures. The results indicate that this method effectively enhanced communication, emotional bonding, and cooperation between parents and children. The activity also stimulated children’s fine motor skills, language abilities, and self-confidence. Evaluation findings showed active participation and high enthusiasm among all participants. Overall, the “Family Stick” activity proved to be an effective method for strengthening harmonious interaction within the family.